The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/reseval/rvt005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dissemination and uptake of clinical trials results

Abstract: A select set of highly-cited publications from the National Institutes of Health (NIH) HIV/AIDS Clinical Trials Networks was used to illustrate the integration of time interval and citation data, modeling the progression, dissemination, and uptake of primary research findings. Following a process marker approach, the pace of initial utilization of this research was measured as the time from trial conceptualization, development and implementation, through results dissemination and uptake. Compared to earlier st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In addition, a recent detailed bibliometric analysis suggests the rapid dissemination of clinical findings. 36 Thus, it is not surprising that most of the T100 articles (58%) in the present study are clinical research, consistent with analyses in other fields. 37–39 The mean citation number per clinical research article was higher than that of basic research articles (404 vs 328).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, a recent detailed bibliometric analysis suggests the rapid dissemination of clinical findings. 36 Thus, it is not surprising that most of the T100 articles (58%) in the present study are clinical research, consistent with analyses in other fields. 37–39 The mean citation number per clinical research article was higher than that of basic research articles (404 vs 328).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, a recently published detailed bibliometric analysis suggests that the dissemination of clinical findings is very rapid. 9 Our limited survey, based on the analysis to identify the citation source for the top three T100 clinical studies, found that most of their citations (2/3) came from other original articles (both clinical and preclinical studies) with the rest of citations (1/3) being found in subsequent reviews, editorials, or meta-analyses. This distribution suggests that conclusions of these highly cited clinical studies had stimulated much subsequent original research.…”
Section: Resultsmentioning
confidence: 99%
“…Approaches to categorization of publications often applied filters based on title words [ 16 18 ]. There have also been efforts to look at citation usage, or knowledge transfer, across categories [ 16 , 19 , 20 ]. More recently, Weber proposed a triangle of biomedicine [ 21 ] where articles are mapped to either humans, animals, or cells and molecules based on the medical subject headings (MeSH) used by PubMed.…”
Section: Introductionmentioning
confidence: 99%